Strategi Penegakan Hukum Tindak Pidana Korupsi Dalam Rangka Membangun Negara Yang Adil dan Makmur - Suratno, Ujang (Yustitia, 2008)
Since its existence, corruptions IS NOT A NEW THING IN Indonesia. There are a lot of problems faced by Indonesia after corruptions becomes a great problem. The longer time of the corruptions in Indonesia it brings influence in co-opting the government system in Indonesia. Law enforcement dealing to corruptions criminal act has been done, but there is still no improvement of reducing corruption problem, it becomes violent and arbitrary. The effect of corruption is very serious , it affects in every fields of life, such as economy, politic, social and also culture , even worse it affects to humanitarianism, so corruption includes to an extra ordinary criminal. Law enforcement now a days has not yet touched the main cause of corruption, even the law upholders sometimes do not know the strength and weakness, and also chance and obstacle in facing up the problem wether consciously or unconsciously, this conditions is aggravated with bad morality. Therefore the perspective of management strategy in eliminating corruption is trying to find out the solution.